Genetic stock structure of white steenbras Lithognathus lithognathus (Cuvier, 1829), an overexploited fishery species in South African waters. Issue 1 (2nd January 2017) - Bennett, RH; Reid, K; Gouws, G; Bloomer, P; Cowley, PD
Abstract : White steenbras Lithognathus lithognathus (Teleostei: Sparidae) is an overexploited marine fish species endemic to South Africa. Overexploitation in recreational, subsistence and commercial fisheries has resulted in stock collapse and the need for improved management of the species. Adults are thought to undertake large-scale annual spawning migrations, yet studies of their movement indicate low levels of connectivity among coastal regions. To address this, mitochondrial DNA sequencing and genotyping of microsatellite loci in the nuclear genome were conducted to determine the genetic stock structure and level of gene flow in this species. Genetic diversity was high throughout the species' core distribution, with no evidence of isolation by way of distance or localised spawning. Low, non-significant pairwise fixation indices ( F ST, R ST and Jost's D est ) indicated low genetic differentiation and high levels of gene flow. The observed results, and agreement between mitochondrial and microsatellite DNA, confirm that white steenbras exists as a single genetic stock with high levels of gene flow throughout its distribution.